PENGEMBANGAN TYPE CURVES MODEL RESERVOIR KOMPOSIT DUA REGION UNTUK BERBAGAI SYARAT BATAS - Hartadi, Adrian
Decline rate type curve or pressure decline type curve with function of time to know and forecast and also analyze reservoir performance has been used practically in fields. These type curves are used in many conditions. This study will develop type curve with any conditions. These conditions are two inner boundary conditions and three outer boundary conditions. Outer boundary conditions are infinite acting reservoir, bounded – no flow reservoir, and bounded – constant pressure at outer boundary. Inner boundary conditions are constant rate and constant pressure well. Type curves were developed by Demski5 and Turki11 previously with two region composite reservoir model in constant pressure. Moreover, Jumiati14 had developed type curves in constant rate but only two outer boundary conditions. Jumiati14 didn’t develop type curves in bounded – constant pressure at outer boundary. Besides, Jumiati14 did not validate the type curves with simulation or field data. In this study, type curves will be developed with any boundary conditions and validated with reservoir simulation CMG (Computer Modelling Group) so that the type curves is true ,validated, and also could be used in all fields or reservoirs. Sensitivity effects which are used in this study are mobility ratio, discontinuity radius, storativity ratio. Type curves could be used for log-log type curve matching interpretation in two regions composite reservoir.